BLOCKSAGE: Blockchain-Based Cloud Architecture for Sensitive Data Management in SMEs - Ascue, Olga (2025)
Small and medium-sized enterprises (SMEs) face significant challenges from security breaches, which can jeopardize their operational sustainability. This study presents the BLOCKSAGE SME system, a model designed to enhance the security of sensitive data storage and transfer. The system integrates customizable cloud infrastructure, private blockchain networks, Zero Trust architecture, a scalable API, and IPFS encryption, ensuring data privacy and business continuity. Based on a comprehensive literature review of blockchain-based solutions for SMEs, a web-based file-sharing prototype was developed and tested to validate the framework. The system was then evaluated through expert judgment and feedback from SME leaders. The results showed a satisfaction score of 4.06 from cybersecurity and blockchain specialists and 4.2 from the target SME audience on a Likert scale, indicating the system’s feasibility and effectiveness. While the system provides robust security measures, adoption challenges were identified, including the early-stage maturity of blockchain technology and cultural and workforce-related barriers within the Peruvian SME ecosystem. In conclusion, the findings suggest that blockchain-based architectures hold strong potential for addressing security gaps in SMEs, but implementation faces current limitations in resources and knowledge. Future research should explore adapting the system as a Software-as-a-Service (SaaS) solution to improve scalability and accessibility, further supporting the sustainability of SMEs.